Mäns våld mot kvinnor och våldets utveckling. En kvalitativ tematisk analys av självbiografier och poddar. - Lavasa,Sofia; Sallah,Mbachu (2025)
The study is focused on intimate partner violence from the woman's perspective and the development of violence. It aimed to explore shared patterns in their experiences, the influence of family and friends, and the women’s perceptions of their self-image and future after the violence. Concentrating on heterosexual relationships across all age groups, the research utilized a thematic analysis of podcasts and autobiographies containing narratives of women who had experienced violence from male partners. The impact of violence on identity and self-image was profound, leading to feelings of shame, worthlessness, and confusion. Many women internalized their partner’s expectations and demands, resulting in diminished self-esteem and a belief that they did not deserve better. Conversely, support from social networks during the process of breaking away from abusive relationships often enabled women to rebuild their self-image positively. Over time, most women regained their sense of self, rebuilt their confidence, and developed new strategies to accept their emotions and regain control over their lives and identities. The study’s findings showed that family and friends play a complex and significant role in these processes. Social support emerged as a crucial factor, with validation and encouragement from family, friends, and other networks helping reduce the risks of continued violence and mental health issues.
Keywords: domestic violence; men's violence against women; normalization process; breakup process; looking-glass self theory